Does the Investment Climate Matter? Microeconomic Foundations of Growth in Latin America - Fajnzylber, Pablo; Guasch, J. Luis; López, J. Humberto (Washington, DC : The World Bank, 2012)
This book aims to fill that gap by using extensive and new firm-level data. It provides an alternative, albeit complementary, approach to previous studies of the determinants of the region's growth performance, which are mostly based on cross-country regressions using aggregate data. This book uses the information contained in enterprise surveys performed in 16 Latin American and Caribbean countries, covering more than 10,000 firms. These data are complemented with information from household surveys, as well as from enterprise surveys performed in other regions of the world. The analysis in this volume covers topics that have also been stressed by other authors, such as the need to make progress in the areas of financial sector development, export promotion, and innovation policy. The book's contribution in this regard is to inform the corresponding policy debates with evidence on the effect of different policy environments on firm performance. Overall this book will contribute to identifying some of the underlying factors that are driving Latin America's lackluster growth performance. In particular, objective is to improve our understanding of the policies that could have a larger influence on increasing growth and productivity in the region, by means of improving the environment in which firms invest and operate.